Moving from cash to cashless economy: Factors affecting digitalization in Nepal - Shrestha, Suman (Nepalese Journal of Management, 2024)
This study examines the factors affecting digitalization in Nepal. A cashless economy is a dependable variable. The selected independent variables are digital payments medium, technology, internet, cybercrime, and security. The primary source of data is used to assess the opinions of the respondents regarding different factors affecting digitalization in Nepal. The study is based on primary data gathered from 121 respondents all over Nepal. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of digitalization in the Nepalese economy. The study showed that digital payments medium has a positive impact on the cashless economy. It indicates that an increase in digital payments medium leads toward a cashless economy. Likewise, the result also showed that technology has a positive impact on a cashless economy. It indicates that technological advancement leads toward a cashless economy. The result also revealed that the internet has a positive impact on a cashless economy. It indicates that the fast and secure internet leads towards a cashless economy. Likewise, the study showed that cybercrime has a negative impact on a cashless economy. It indicates that a decrease in cybercrime leads towards a cashless economy. Further, the study showed that security has a positive impact on a cashless economy. It indicates that highly secured network leads toward a cashless economy.